Static Load Simulation for Optimizing Automatic Fish Cracker Dough Mixing Machine Design: Simulasi Beban Statis untuk Mengoptimalkan Desain Mesin Pencampur Adonan Kerupuk Ikan Otomatis - Mohamad Irvan Akif Setiawan; Mulyadi; A'rasy Fahruddin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Fish crackers are a popular Indonesian snack with a simple production process but high demand. Specific Background In Pasuruan Regency, SMEs struggle with manual dough mixing, which leads to inconsistent texture and high labor costs. Knowledge Gap Current traditional methods lack efficiency and structural consistency, requiring a more robust and hygienic automated solution. Aims This study aims to design and validate an automatic fish cracker dough mixing machine using static load simulations. Results The selection process using a morphological chart led to Concept A, which utilizes a 0.37 kW motor and stainless steel components. SolidWorks 2016 simulations revealed a maximum von Mises stress of 14.224 MPa and a maximum displacement of 8.74 mm under a 92 Nm torque load. Novelty The research introduces a highly stable frame structure (50x50x3 mm profile) with a safety factor of 13, significantly exceeding standard safety requirements for SME equipment. Implications This innovation allows for consistent 10 kg batch production, reducing manual labor and increasing the profit potential for local food industries. Keywords Dough Mixer, Fish Crackers, Morphological Chart, Static Simulation, Safety Factor Key Findings Highlights Concept A was selected as the optimal design using a systematic morphological chart and FEA validation. The frame structure achieves a safety factor of 13, ensuring high durability for small-scale industrial use. The automated system replaces manual labor with a 0.37 kW motor capable of handling 10 kg loads efficiently.